High-temperature-resistant organic gold slurry and infrared reflection gold coating
By using organic chromium, organic bismuth, organic copper and organic yttrium as high-temperature resistance additives in organic gold pastes, the problem of instability of the film structure of existing organic gold coatings under high temperature conditions has been solved, and cost reduction and performance improvement have been achieved.
Patent Information
- Application Number
- CN202411463941.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The film structure of existing organic gold coatings is unstable under high temperature conditions, resulting in defects and increased costs, making it difficult to replace the high-cost rhodium element.
Organic chromium, organic bismuth, organic copper and organic yttrium are used as high-temperature-resistant organometallic additives to replace rhodium elements to form a high-temperature-resistant diffusion barrier layer to maintain the stability of the gold film structure.
It effectively reduces the cost of organic gold paste, improves the high temperature resistance and adhesion of the gold coating, maintains the optical properties and infrared reflectivity of the gold coating, and has a reflectivity of up to 96%.
Smart Images

Figure CN119541921A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating slurries, and in particular relates to a high temperature resistant organic gold slurry and a gold coating for infrared reflection. Background Art
[0002] Gold has good chemical stability, high conductivity and excellent ductility. It is widely used in many fields such as electronics, optics, semiconductor epitaxial growth equipment, construction engineering and aerospace engineering. In these applications, gold usually exists in the form of thin films. The methods for preparing gold thin films mainly include physical and chemical methods, such as physical vapor deposition methods such as thermal evaporation, electron beam deposition, magnetron sputtering, and electrochemical deposition. Although these methods can prepare high-quality gold films, the cost of physical vapor deposition is high and it is difficult to apply to complex structure surfaces, while the electrochemical deposition method requires the substrate to be conductive, which limits the application field of gold thin films.
[0003] The organic gold paste prepared with organic gold is applied to the surface of the object by brushing or spraying, and finally annealed to obtain a gold coating. This method is applicable to surfaces with complex structures, and the color of the film can be adjusted according to needs, effectively solving the problems existing in physical vapor deposition and electrochemical deposition methods.
[0004] Although the invention of organic gold coating has a history of more than 100 years, its main components have changed little. The main components are organic gold molecules (including resin gold, thiol gold, etc.), and also include metal additives that enhance the adhesion of the gold coating, such as chromium (Cr), bismuth (Bi), indium (In) and tin (Sn) to prevent gold particles from agglomerating; palladium (Pd) and rhodium (Rh) are used to keep the film uniform; iron (Fe), zinc (Zn) and titanium (Ti) are used to control the color of the film. For example, the invention application with publication number CN113921165A discloses an organic gold slurry, which contains trifunctional thiol resin acid gold, resin acid rhodium, resin acid palladium, organic metal compound additives and organic carriers, wherein the rhodium element is conducive to obtaining a dense, bright, crack-free, and excellently conductive film after sintering. The reason is that metal rhodium (Rh) exists in the form of oxide at the grain boundaries of gold particles, which can effectively prevent the fusion of adjacent gold particles at high temperatures and maintain the stability of the film structure, thereby allowing the gold coating to withstand higher annealing temperatures, reducing gold coating defects, ensuring the optical properties of the gold coating, and improving adhesion to the substrate surface.
[0005] During the conversion of organic gold coating into gold coating, different organic substances can decompose in different temperature intervals, wherein the decomposition temperature of resin acid rhodium is higher than other organic metals, but lower than the resin in the coating, rhodium oxide can be formed under certain temperature conditions and coated on the surface of gold particles, which can effectively prevent the fusion of adjacent gold particles under high temperature. Although the addition amount of rhodium is less, its price is higher, which increases the cost of coating to a certain extent. Therefore, it is necessary to develop other organic metal additives to replace rhodium and reduce the cost of organic gold slurry. For example, the invention application with publication number CN114639501A discloses a low-cost organic gold slurry, and the coating is mainly composed of resin acid gold, resin acid tin, resin acid erbium, resin acid bismuth, resin acid chromium, resin acid iron, and resin acid manganese. Wherein the composite action of resin acid tin and resin acid erbium can make the film withstand high temperature without cracks, replaces resin acid rhodium, and maintains the stability of the film structure.
[0006] Based on the decomposition process of organic gold, more high-temperature resistant metal additives are developed to form a high-temperature resistant diffusion barrier layer on the surface of gold particles to maintain the stability of the gold film structure, thereby improving the flexibility of organic gold coating formulation and reducing costs. This is an urgent problem that needs to be solved in the field of gold coatings. Summary of the invention
[0007] The purpose of the present invention is to provide a high temperature resistant organic gold slurry and an infrared reflective gold coating, which is used to develop more high temperature resistant metal additives, maintain the structural stability of the gold coating film, and improve the flexibility of the organic gold coating preparation.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0009] The invention provides a high temperature resistant organic gold slurry, comprising resin acid gold, resin, organic solvent and organic metal additive, wherein the organic metal additive consists of organic chromium, organic bismuth, organic copper and organic yttrium, wherein the mass percentage of the organic metal additive is 1.5%-3%, and the mass ratio of the organic chromium, organic bismuth, organic copper and organic yttrium in the organic metal additive is 1.1:1.3:0.3:0.3.
[0010] Preferably, the mass percentage of the resin acid gold in the high temperature resistant organic gold paste is 20%-30%; the mass percentage of the resin is 10%-20%.
[0011] Preferably, the gold resinate is obtained by reacting sulphurized balsam with gold chlorate. For the specific preparation method, reference may be made to the invention patents with publication numbers CN117316491A and CN112735631A.
[0012] Preferably, the resin includes one or more of terpene resin, epoxy resin, acrylic resin, alkyd resin and rosin resin.
[0013] Resin has good adhesion and high temperature resistance, and is widely used in the adhesive field to enhance the hardness and wear resistance of the coating. In addition, resin has good mechanical properties and is widely used in packaging materials, optical materials and other electronic components.
[0014] Preferably, the organic solvent is one or more of terpineol, linalool, camphor oil, turpentine, ethylene glycol monobutyl ether, dibutyl phthalate and trichloroethane.
[0015] As a volatile component, the organic solvent can provide polar groups and prevent the slurry from coagulating and deteriorating during long-term storage. It is used to mix the organic metal additives and other solid powders to form a paste slurry.
[0016] Preferably, the organic yttrium is selected from one or both of yttrium isooctanoate and yttrium neodecanoate;
[0017] Preferably, the organic bismuth is selected from one or both of bismuth isooctanoate and bismuth neodecanoate.
[0018] Bismuth isooctanoate or bismuth neodecanoate has good stability in high temperature and acidic environment and is not easy to decompose, which can improve the chemical resistance and high temperature resistance of the material.
[0019] Preferably, the organic chromium is selected from one or both of chromium isooctanoate and chromium neodecanoate.
[0020] Chromium 2-ethylhexanoate and chromium neodecanoate can be used as rust inhibitors on metal surfaces to enhance oxidation resistance and corrosion resistance and improve processing quality and efficiency.
[0021] Preferably, the organic copper is selected from one or both of copper octanoate and copper neodecanoate.
[0022] Copper isooctanoate and copper neodecanoate can be used as paint additives to improve the conductivity of the paint.
[0023] The present invention also proposes a method for preparing a gold coating for infrared reflection, which uses the high-temperature resistant organic gold slurry; the method for preparing the infrared reflection gold coating comprises: applying the high-temperature resistant organic gold slurry on the surface of a high-temperature resistant substrate by brushing or spraying, leveling, and then annealing to obtain a gold coating.
[0024] Brushing or spraying is suitable for high-solids, high-viscosity coatings and can be used to coat complex shapes with great flexibility.
[0025] Preferably, the leveling is performed at room temperature for 10-30 minutes.
[0026] The room temperature leveling method can prompt the paint to form a flat, smooth and uniform coating film during the drying process, thereby improving the decorative and protective functions of the paint.
[0027] Preferably, the annealing process includes two steps of heating, the first step is a heating temperature of 80-100°C, and the heating time is 10 minutes; the second step is a heating temperature of 750-850°C, and the heating time is 10 minutes; the heating rate during the annealing process is 10°C / min, and after the heating is completed, the temperature is naturally cooled, and the sample is taken out when the temperature drops below 100°C to obtain a gold coating for infrared reflection.
[0028] The purpose of the first step annealing treatment is to keep the slurry fixed after leveling, which is conducive to the subsequent second step treatment.
[0029] Further preferably, the first step heating temperature is 80° C., and the heating time is 10 min; the second step heating temperature is 850° C., and the heating time is 10 min.
[0030] The invention also proposes a gold coating for infrared reflection prepared based on the method.
[0031] The invention also proposes the application of the infrared reflective gold coating in a coating reactor.
[0032] The beneficial effects of the present invention are:
[0033] The present invention provides a high temperature resistant organic gold paste, which uses organic yttrium as a high temperature resistant organic metal additive to prepare the organic gold paste. The obtained organic gold paste has excellent high temperature resistance and effectively reduces the cost of the organic gold paste.
[0034] The method for preparing a gold coating for infrared reflection provided by the present invention uses a high-temperature resistant organic gold slurry to withstand a higher annealing temperature, reduce the defects of the gold coating, and maintain the stability of the gold coating; the prepared gold coating has good adhesion and excellent infrared reflection performance on the quartz surface, wherein organic yttrium is used as a high-temperature resistant organic metal additive to achieve good high-temperature resistance, and the reflectivity of the obtained gold coating in the near-infrared region can reach 96%, while maintaining the optical properties of the gold coating, effectively reducing the cost of the organic gold coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is an optical picture of the gold coating, where Figure 1 A in the figure is an optical picture of gold coating prepared with different high temperature resistant agents; Figure 1 B in the figure is an optical image of a gold coating prepared on a cylindrical quartz surface using yttrium-gold slurry.
[0036] Figure 2Microstructural characterization of the gold coating prepared by the organic gold paste prepared in Example 1 at different annealing temperatures.
[0037] Figure 3 Near-infrared reflectance properties of gold coatings prepared for different high temperature agents.
[0038] Figure 4 Near-infrared reflection properties of gold coatings prepared at different annealing temperatures.
[0039] Figure 5 To characterize the adhesion of gold coatings prepared from yttrium-gold slurries on quartz surfaces, Figure 5 A in the figure is the adhesion strength curve of the gold coating prepared on the quartz surface by the yttrium-gold slurry; Figure 5 B is an optical microscope image of the scratches on the gold coating prepared with yttrium-gold slurry.
[0040] Figure 6 The gold coating photos of the organic gold pastes prepared in Comparative Examples 3 and 4 are shown in FIG. Figure 6 A is a gold coating prepared from a yttrium-containing gold slurry with 0.1 wt%; Figure 6 B in the figure is a gold coating prepared without organic metal additives. DETAILED DESCRIPTION
[0041] Example 1
[0042] The preparation method of yttrium-containing organic gold slurry is as follows:
[0043] Gold resinate (YDAUP002, Industrial Technology Research Institute) was added to a mixed solution of pineol and linalool, wherein the mass ratio of pineol to linalool was 1:1, and a stable solution was obtained by magnetic stirring, namely, the gold resinate solution.
[0044] The terpene resin is added to the pine alcohol solution and dispersed by ultrasound to form a uniform and stable solution, which is the resin solution.
[0045] The resin solution is added to the resin acid gold solution, and the organic metal additives chromium isooctanoate, bismuth isooctanoate, copper isooctanoate and yttrium isooctanoate are added and mixed thoroughly to prepare an organic gold coating containing 30wt% of resin acid gold, 20wt% of terpene resin, 1.1wt% of chromium isooctanoate, 1.3wt% of bismuth isooctanoate, 0.3wt% of copper isooctanoate and 0.3wt% of yttrium isooctanoate.
[0046] Example 2
[0047] The organic gold paste is prepared in the same manner as in Example 1, except that the resin acid gold is 20 wt % to obtain the organic gold paste.
[0048] Example 3
[0049] The organic gold paste is prepared in the same manner as in Example 1, except that the resin is 10 wt %.
[0050] Example 4
[0051] The organic gold slurry preparation method is the same as that in Example 1, the difference is that the mass ratio of chromium isooctanoate, bismuth isooctanoate, copper isooctanoate and yttrium isooctanoate is 1.1:1.3:0.3:0.3, wherein the yttrium isooctanoate is 0.15wt%, and the organic gold slurry is prepared.
[0052] Example 5
[0053] The method for preparing an organic gold paste is the same as that in Example 1, the mass ratio of chromium isooctanoate, bismuth isooctanoate, copper isooctanoate and yttrium isooctanoate is 1.1:1.3:0.3:0.3, wherein the yttrium isooctanoate is 0.1wt%, and the organic gold paste is prepared.
[0054] Comparative Example 1
[0055] The preparation method of rhodium-containing organic gold slurry is as follows:
[0056] The organic gold slurry preparation method of Example 1 is used to prepare an organic gold coating by replacing yttrium isooctanoate with rhodium isooctanoate and keeping the components of other organic metal additives unchanged.
[0057] Comparative Example 2
[0058] The preparation method of zirconium-containing organic gold slurry is as follows:
[0059] The organic gold slurry preparation method of Example 1 is as follows, except that yttrium isooctanoate is replaced by zirconium isooctanoate, and the components of other organic metal additives remain unchanged, to prepare an organic gold coating.
[0060] Comparative Example 3
[0061] The preparation method of organic gold paste without high temperature resistant agent is as follows:
[0062] The organic gold paste preparation method of Example 1 is as follows, except that yttrium isooctanoate is removed and the components of other organic metal additives in the organic gold paste remain unchanged to prepare an organic gold coating.
[0063] Test Example 1
[0064] Preparation of gold coating with organic gold slurry: The organic gold slurries obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were evenly brushed on the surface of the quartz substrate, respectively, and placed at room temperature in a clean environment for 10-30 minutes. The samples were transferred to an annealing furnace for a two-step annealing treatment.
[0065] The specific annealing process is as follows: the first step of annealing is to heat up to 80°C at a heating rate of 10°C / min and heat for 10 minutes; then continue to raise the temperature to 850°C at a heating rate of 10°C / min and heat for 10 minutes. After heating is completed, wait for the annealing furnace temperature to drop below 100°C, take out the sample, and you can get a gold coating.
[0066] Another group of gold coatings were subjected to two-step annealing treatment. The first step of annealing treatment was to heat the temperature to 100°C at a heating rate of 10°C / min for 10 minutes; then the temperature was raised to 850°C at a heating rate of 10°C / min for 10 minutes. After heating, the annealing furnace temperature dropped below 100°C, and the samples were taken out to obtain the gold coating. The first step of annealing treatment is to keep the slurry fixed after leveling, which is conducive to the subsequent second step. If there is no subsequent indication, the default first step annealing temperature is 80°C and the second step annealing temperature is 850°C.
[0067] like Figure 1 As shown, the optical pictures of the gold coating prepared by the organic gold paste of Example 1 and Comparative Examples 1 to 3 and the optical picture of the gold coating prepared by the organic gold paste containing yttrium (Example 1) on the cylindrical quartz surface. The results show that when zirconium (Comparative Example 2) is used as a high temperature resistant agent, the color of the obtained gold coating film is reddish, and when yttrium and rhodium (Example 1 and Comparative Example 1) are used as high temperature resistant agents, the color difference of the gold coating is small, which does not affect the appearance characteristics of the coating, and can replace the high-cost gold coating of the same color.
[0068] Test Example 2
[0069] The microstructure of the gold coating prepared by the organic gold paste prepared in Example 1 at different annealing temperatures and different numbers of layers was characterized by a scanning electron microscope (SEM). The method for preparing the gold coating was the same as that in Test Example 1, wherein the annealing temperature was set at 450°C or 850°C to prepare a single-layer gold coating. In another group of experiments, the brushing and annealing steps of the organic gold paste were repeated under the condition that the annealing temperature was set at 850°C. On the basis of preparing a single-layer gold coating, the three-layer gold coating was obtained by repeating the process twice.
[0070] The results are as follows Figure 2 As shown, specifically: the single-layer gold coating with an annealing temperature of 450°C and the single-layer and triple-layer gold coatings with an annealing temperature of 850°C are characterized respectively.
[0071] The results show that the thickness of a single-layer gold coating prepared by annealing the yttrium-containing organic gold slurry at 450°C is about 130nm, and the thickness of a single-layer gold coating prepared by annealing the yttrium-containing organic gold slurry at 850°C is about 100nm. The gold coating prepared by annealing at 450°C has more surface defects, indicating that the higher the annealing temperature, the fewer microscopic defects in the coating and the denser the coating, which is beneficial to improving the corrosion resistance of the coating and extending the service life of the gold coating.
[0072] Test Example 3
[0073] The method for preparing the gold coating is the same as that in Test Example 1, and the near-infrared reflection properties of the gold coatings prepared with different high-temperature resistant agents are analyzed. Figure 3 Shown is the infrared reflectivity of the high temperature resistant agents yttrium, rhodium and zirconium. The measured reflectivity is a relative value, with the evaporated gold coating as the benchmark.
[0074] The results show that in the near-infrared region of 1000-2500nm, the reflectivity of rhodium as a high-temperature resistant agent can reach 98%; yttrium can reach 96%; the reflectivity of zirconium is slightly lower, about 90% or more, indicating that when yttrium is used as a high-temperature resistant agent, the near-infrared reflection performance of the gold coating is close to that of rhodium, which can reduce the cost of high-temperature resistant gold coatings.
[0075] Test Example 4
[0076] The near-infrared reflection performance of the gold coating prepared at different annealing temperatures was analyzed. The method for preparing the gold coating is the same as that in Test Example 1, the high temperature resistant agent is yttrium, and the annealing temperature of the yttrium high temperature resistant agent gold coating is set to 750°C or 850°C. Figure 4 Shown is the near-infrared reflectivity of the gold coating prepared at different annealing temperatures. The measured reflectivity is a relative value, with the evaporated gold coating as a benchmark.
[0077] The results show that in the near-infrared region of 1000-2500nm, the near-infrared reflection performance of the yttrium-containing high-temperature resistant gold coating prepared at 750℃ or 850℃ annealing temperature is similar.
[0078] Test Example 5
[0079] The method for preparing the gold coating is the same as that in Test Example 1. The adhesion of the coating determines the life of the coating. Therefore, a scratch instrument is used to characterize the adhesion strength of the prepared gold coating on the quartz surface. The surface adhesion strength of the coating refers to the strength of the bonding between the coating and the substrate, that is, the energy required for the coating per unit surface area to peel off from the substrate (or intermediate coating). The bonding strength between the coating and the substrate is an important indicator of the coating performance. If the bonding strength is low, it will cause the coating life to be reduced, premature failure, or the coating to fall off (peel) and cannot be used.
[0080] like Figure 5 As shown, the adhesion strength of the gold coating containing the high temperature resistant agent yttrium is 33J / m 2 The bonding strength between pure gold and silicon oxide is 0.39 J / m 2 ; The energy density generated by the difference in thermal expansion coefficients of the quartz surface with a gold coating of 100 nm thickness at a temperature difference of 850°C is 0.90 J / m 2Therefore, the obtained gold coating containing the high temperature resistant agent yttrium has greater adhesion and stronger high temperature impact resistance.
[0081] Test Example 6
[0082] The method for preparing the gold coating is the same as that in Example 1. Figure 6 Shown are gold coatings prepared by the organic gold slurries of Comparative Example 3 and Example 5. The results show that when the yttrium isooctanoate content is low or removed, the surface of the gold coating is unevenly distributed. When the yttrium content is 0.1wt%, there is aggregation in the coating. The gold coating without organic yttrium cannot form a complete film, and the defects in the film will produce stress concentration points, which will cause the coating to fall off and fail.
Claims
1. A high temperature resistant organic gold paste, comprising resin acid gold, resin, organic solvent and organic metal additive, characterized in that: The components of the organic metal additive are composed of organic chromium, organic bismuth, organic copper and organic yttrium, wherein the mass percentage of the organic metal additive is 1.5%-3%, and the mass ratio of organic chromium, organic bismuth, organic copper and organic yttrium in the organic metal additive is 1.1:1.3:0.3:0.
3.
2. The high temperature resistant organic gold paste according to claim 1, characterized in that: The mass percentage of the resin acid gold in the high temperature resistant organic gold paste is 20%-30%; the mass percentage of the resin is 10%-20%.
3. The high temperature resistant organic gold paste according to claim 1, characterized in that: The resin acid gold is obtained by reacting gold chlorate with sulfurized balsam.
4. The high temperature resistant organic gold paste according to claim 1, characterized in that: The resin includes one or more of terpene resin, epoxy resin, acrylic resin, alkyd resin and rosin resin.
5. The high temperature resistant organic gold paste according to claim 1, characterized in that: The organic solvent is one or more of terpineol, linalool, camphor oil, turpentine, ethylene glycol monobutyl ether, dibutyl phthalate and trichloroethane.
6. A method for preparing a gold coating for infrared reflection, characterized in that: Using the high temperature resistant organic gold paste according to any one of claims 1 to 5; The method for preparing the infrared reflective gold coating comprises: applying the high temperature resistant organic gold slurry on the surface of the high temperature resistant substrate by brushing or spraying, leveling, and then performing an annealing process to obtain the gold coating.
7. The method for preparing an infrared reflective gold coating according to claim 6, characterized in that: The leveling is performed at room temperature for 10-30 minutes.
8. The method for preparing a gold coating for infrared reflection according to claim 6, characterized in that: The annealing process includes two steps of heating, the first step of which is at a heating temperature of 80-100°C and a heating time of 10 minutes; the second step of which is at a heating temperature of 750-850°C and a heating time of 10 minutes; the heating rate during the annealing process is 10°C / min, and after the heating is completed, the temperature is naturally lowered, and the sample is taken out when the temperature drops below 100°C to obtain a gold coating for infrared reflection.
9. A gold coating for infrared reflection prepared according to the method of any one of claims 6 to 8.
10. Use of the infrared reflective gold coating according to claim 9 in a coating reactor.
Citation Information
Patent Citations
Low-viscosity organic gold paste capable of being sintered on surface of circuit board substrate at low temperature
CN112735631A
Organic gold slurry
CN113921165A
Low-cost organic gold paste
CN114639501A
Organic gold paste easy to form film as well as preparation method and application of organic gold paste
CN117316491A
Print-on pastes with metal-based additives for modifying material properties of metal particle layers
CN112384992A